A Comparison of The Learning Outcomes Resulted from Jigsaw and TSTS Learning Models Viewed from The Students’ Self Regulated Learning - Putratama, Alfadeo Adi; Sutriyono, Sutriyono; Pratama, Fika Widya (International Journal of Active Learning, 2019)
This is a quasi experimental research aiming to compare the learning outcomes resulted from Jigsaw and Two Stay Two Stray learning models in the context of self regulated learning. The objectives of this research are to investigate (1) whether there is an influence of the learning model on the learning outcomes, (2) whether there is an influence of self regulated learning on the mathematics learning outcomes, and (3) whether there is an interaction between the learning models (Jigsaw and TSTS) and self regulated learning. The population of this research was the eleventh graders of SMA 1 Bringin having the mathematical induction lesson. By employing the cluster random sampling technique, two MIPA (math and science program) classes were selected to be the research subjects. The XI MIPA 2 class was set to be the experimental class, and XI MIPA 4 as the comparison. This research employed the Randomized Control Pretest-Posttest Design Group, the Kolmogorov-Smirnov method to test normality, Leven's method to test homogeneity, and Independent Sample T-Test to test the initial balance of ability. The statistical test program used in this research was SPSS version 24 with 5% significance level. The results of hypothesis testing concluded that (1) there were no differences in the learning outcomes resulted from the cooperative learning model implementation, (2) there were differences in the learning outcomes in the context of self regulated learning, and (3) there was no interaction between the learning models and self regulated learning.